An investigation into the predictive power of reflective thinking on learning strategies. Issue 2 (4th March 2023) - Aydoğmuş, Mevlüt; Şentürk, Cihad
ABSTRACT: The purpose of this study is to examine the relationship between secondary school students' reflective thinking skills and their learning strategies, as well as to assess the predictive power of reflective thinking on learning strategies. A correlational survey model was used in the study. The participants consisted of 378 students studying in secondary schools in Konya, in the 2021–2022 academic year. The study found that there were positive relationships between the students' reflective thinking skills and the sub-dimensions of learning strategies. In addition, structural equation model analysis indicated that the model was significant as a whole and students' reflective thinking skills and learning strategies were significantly correlated. In the model tested, it was found that reflective thinking positively predicted learning strategies and reflective thinking explained 72% of the change in learning strategies. According to these results, it can be argued that students' reflective thinking skills play a key role in the formation and shaping of learning strategies.